Pertanggungjawaban Pidana Korporasi dalam Kasus Lingkungan Hidup di Indonesia Tinjauan Yuridis Undang-Undang Nomor 32 Tahun 2009 dan Perma Nomor 1 Tahun 2023 - Rohmat, Dedin ; Aminudin, Cecep (HUMANIORUM, 2025)
The environment plays an important role in human life now and in the future. Therefore, various environmental protection efforts are an important concern for stakeholders in Indonesia through regulations or legislation as part of law enforcement and preventive measures including Law Number 32 of 2009 concerning environmental protection and management to the latest regulation, namely Supreme Court Regulation Number 1 of 2023 (Perma Number 1 of 2023). This journal is written using two approaches, namely the regulatory approach (statute approach) and the conceptual approach (conceptual approach) which is supported by secondary data collection techniques through library research, both from books, journals or official websites. This journal shows that the role of Law Number 32 of 2009 is intended as a systematic effort to systematically preserve the environment to prevent environmental pollution and damage, while Perma Number 1 of 2023 is a law that can accommodate various advanced corporate criminal issues related to environmental cases that have just emerged in the early 2020s, including the destruction of coastal and forest ecosystems, pollution to violations of applicable regulations, including errors in the processing of B3 waste which opens up law enforcement, both criminal and civil, more fundamentally, effectively and systematically.